Seasons of Migration to the East. Issue 4 (June 2015) - Abdelrahman, Mohamed; Lukavsky, Robert; Chen, Yu-Ray
<x xml:space="preserve">Abstract</x> Fellowship is becoming a mainstay in the road of career development, though it has not been studied thoroughly. There was an opportunity to study these unresearched questions in the context of the Craniofacial Surgery International Fellowship at Chang Gung Memorial Hospital. An example of planned temporary migration for specific training. In this study, we look at the special case of Craniofacial Surgery Fellowship at Chang Gung Memorial Hospital in Taiwan, which completes three decades by this year (1984–2014). There is a dearth of published literature on the issue of fellowship training.